2003
DOI: 10.1055/s-2003-37188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyaluronic Acid-Carboxymethylcellulose Membrane on Extraneural Adhesion Formation and Peripheral Nerve Regeneration

Abstract: The goal of nerve repair in the peripheral nervous system is to increase the number of axons passing from proximal to distal stump, and to enable the regenerated axons to reach the end organ as soon as possible. In the present study, the effect of the membrane formed by a mixture of hyaluronic acid and carboxymethylcellulose (HA-CMC) on nerve regeneration and perineurial scar formation was investigated. Eighteen New Zealand rabbits were allocated into control (n = 9) and experimental groups (n = 9). In the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 14 publications
1
54
2
Order By: Relevance
“…7,8,[17][18][19] The role of HACM may be therapeutic as well as protective. The 2003 study by Adanali and colleagues 9 concluded that HACM use with concurrent repair of sciatic nerve injuries in rabbits resulted in a statistically significant improvement in the number of viable axons 3 months after surgery and a reduction in perineural fibrosis. 9 The introduction of a locally active agent as a physical barrier around the NVBs to separate them from adjacent inflammatory tissue and reduce fibrosis is a novel concept.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8,[17][18][19] The role of HACM may be therapeutic as well as protective. The 2003 study by Adanali and colleagues 9 concluded that HACM use with concurrent repair of sciatic nerve injuries in rabbits resulted in a statistically significant improvement in the number of viable axons 3 months after surgery and a reduction in perineural fibrosis. 9 The introduction of a locally active agent as a physical barrier around the NVBs to separate them from adjacent inflammatory tissue and reduce fibrosis is a novel concept.…”
Section: Discussionmentioning
confidence: 99%
“…The 2003 study by Adanali and colleagues 9 concluded that HACM use with concurrent repair of sciatic nerve injuries in rabbits resulted in a statistically significant improvement in the number of viable axons 3 months after surgery and a reduction in perineural fibrosis. 9 The introduction of a locally active agent as a physical barrier around the NVBs to separate them from adjacent inflammatory tissue and reduce fibrosis is a novel concept. Unlike an individual's surgical technique, HACM use can be standardized in its dosage, delivery, and target area to improve early potency outcomes after RARP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the peripheral nerves, HA is one of the prominent components of the Bunger band formed during Wallerian degeneration, and the ablation of HA receptors can reduce cell adhesion and migration [15]. Several studies showed that HA has a positive effects on peripheral nerve regeneration [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…2 An HA-carboxymethylcellulose membrane has also been shown to decrease the formation of both intraand extraneural fibrosis in rabbits. 3 Hyaloglide 1 (Fidia Advanced Biopolymers, Abano Terme, Italy) is a crosslinked hyaluronan gel that is both biocompatible and bioreabsorbable, with a degradation pathway equivalent to HA. It also has improved viscoelastic properties compared to unmodified HA solutions of the same molecular weight.…”
mentioning
confidence: 99%